2005
DOI: 10.1007/s00442-005-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Community assembly at the patch scale in a species rich tropical river

Abstract: In tropical floodplain rivers, communities associated with structurally complex habitats are disassembled and reassembled as aquatic organisms repeatedly colonize new areas in response to gradual but continuous changes in water level. Thus, a neutral model reflecting random colonization and extinction dynamics may be sufficient to predict assemblage patterns at the scale of local habitat patches. If water level fluctuations and associated patch dynamics are sufficiently predictable, however, community assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
1
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 49 publications
11
126
1
11
Order By: Relevance
“…Flecker (1992 reported rapid colonization of manipulated substrata by invertebrates in a piedmont river in Venezuela, with from 600 to > 2400 individuals per 0.25 m 2 . Crenicichla lugubris in the Cinaruco River were common near submerged woody debris and rocks, and these habitats probably hold relatively sedentary prey Arrington et al, 2005). These structurally in the Cinaruco River and Layman et al (in press) in the nearby Caño La Guardia.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Flecker (1992 reported rapid colonization of manipulated substrata by invertebrates in a piedmont river in Venezuela, with from 600 to > 2400 individuals per 0.25 m 2 . Crenicichla lugubris in the Cinaruco River were common near submerged woody debris and rocks, and these habitats probably hold relatively sedentary prey Arrington et al, 2005). These structurally in the Cinaruco River and Layman et al (in press) in the nearby Caño La Guardia.…”
Section: Discussionmentioning
confidence: 82%
“…During the wet season (May to October), the riparian forest and surrounding savanna is flooded, and organisms disperse widely throughout the river floodplain. The dry season is associated with a continuously falling water level that forces aquatic organisms off the floodplain and into the main river channel and lagoons (Winemiller & Jepsen, 1998;Arrington et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Two main assemblages were identified in Taraira Lake, a large assemblage of species associated with lagoon channels, stream, isolated shrub patches and flooded forest habitats; and a second assemblage of species associated with muddy beaches. Non-random associations of fish species have seemingly been found in other seasonal system, influenced by characteristics of the habitat and by interspecific interactions (Rodriguez & Lewis, 1997;Petry et al, 2003;Arrington et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Layman and Winemiller (2004) found direct evidence for the influence of predator abundance on medium-size prey fishes in beach communities of a lowland river in Venezuela during the low-water season. Arrington et al (2005) found evidence for species interactions influencing fish assemblage structure mediated by dispersal dynamics in response to changing water levels in a floodplain river in the Venezuelan llanos.…”
Section: Introductionmentioning
confidence: 91%
“…Durante o período de cheia muitas espécies de peixes tendem a se dispersar ao longo da planície inundada para explorar novos hábitats e recursos alimentares (SAINT-PAUL et al 2000, SILVANO et al 2000, GALACATOS et al 2004, ARRINGTON et al 2005. Na seca, com a diminuição do nível da água, os peixes estão mais concentrados nos ambientes e são mais facilmente capturados pelas redes de espera (GOULDING et al 1988, SILVANO et al 2000.…”
Section: Estrutura Da Ictiofaunaunclassified